Sedimentary evolution and paleoclimate conditions in the Yangtze river estuary across the late Pleistocene to early Holocene - Siqi Li; Gaoyuan Sun; Jianuo Chen; Kai Liu; Ren Jiang; Xiaohua Zhou; Tianchen He (Frontiers in Marine Science, 2026)
Due to the complexity of sedimentary evolution since the Last Glacial Maximum (LGM) in the Yangtze River Estuary (YRE), sedimentary responses across different regions have varied significantly, but the sedimentary record on the northern flank of the estuary remains incomplete. Here we integrate analyses of sedimentology, chemical weathering indices (CIA and K/Al), total organic carbon (TOC), and organic carbon isotopes (δ 13 C org ) from the QDQ2 core to reconstruct the regional environmental evolution from 36.1 to 8.4 cal kyr BP. Facies analysis demonstrates that QDQ2 succession documents environmental shift from terrestrial distributary channels to marine delta fronts. Sedimentary evidence of marine transgression during the Last Deglacial Period is identified, and facies shifts were driven by climate events and sea-level variations. Furthermore, the Gehu transgression did not influence the facies succession of study area. Instead, variations in CIA and K/Al ratios indicate modification in the hinterland chemical weathering intensity, likely driven by the warm climate characteristics of Marine Isotopic Stage 3a (MIS 3a).